2023
DOI: 10.1101/2023.02.01.526536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

tRNA m1G9 modification depends on substrate-specific RNA conformational changes induced by the methyltransferase Trm10

Abstract: The methyltransferase Trm10 modifies a subset of tRNAs on the base N1 position of the 9th nucleotide in the tRNA core. Trm10 is conserved throughout Eukarya and Archaea, and mutations in the human gene (TRMT10A) have been linked to neurological disorders such as microcephaly and intellectual disability, as well as defects in glucose metabolism. Of the 26 tRNAs in yeast with guanosine at position 9, only 14 are substrates for Trm10. However, no common sequence or other posttranscriptional modifications have bee… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…Recently, we have obtained some insight into at least one of the factors that seems to be associated with tRNA selection by Trm10 in vitro . The selective 2′-OH acylation analyzed by primer extension (SHAPE) reactivity of five in vitro transcribed tRNAs was evaluated, comparing the observed reactivities of the free tRNA to the tRNA bound by Trm10 . The studied transcripts included two in vivo substrates of S. cerevisiae Trm10, tRNA Gly GCC and tRNA Trp CCA , a tRNA only modified in vitro , tRNA Val UAC , and two tRNAs that are not modified by Trm10 in vitro or in vivo , tRNA Leu CAA and tRNA Ser UGA .…”
Section: Diversity In Trna Substrate Recognition By Trm10mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have obtained some insight into at least one of the factors that seems to be associated with tRNA selection by Trm10 in vitro . The selective 2′-OH acylation analyzed by primer extension (SHAPE) reactivity of five in vitro transcribed tRNAs was evaluated, comparing the observed reactivities of the free tRNA to the tRNA bound by Trm10 . The studied transcripts included two in vivo substrates of S. cerevisiae Trm10, tRNA Gly GCC and tRNA Trp CCA , a tRNA only modified in vitro , tRNA Val UAC , and two tRNAs that are not modified by Trm10 in vitro or in vivo , tRNA Leu CAA and tRNA Ser UGA .…”
Section: Diversity In Trna Substrate Recognition By Trm10mentioning
confidence: 99%
“…The selective 2′-OH acylation analyzed by primer extension (SHAPE) reactivity of five in vitro transcribed tRNAs was evaluated, comparing the observed reactivities of the free tRNA to the tRNA bound by Trm10. 41 The studied transcripts included two in vivo substrates of S. cerevisiae Trm10, tRNA Gly GCC and tRNA Trp CCA , a tRNA only modified in vitro, tRNA Val UAC , and two tRNAs that are not modified by Trm10 in vitro or in vivo, tRNA Leu CAA and tRNA Ser UGA . 1 SHAPE data revealed that when Trm10 binds to a catalytically competent substrate tRNA, the D-stem becomes more flexible, potentially to allow the enzyme access to the core G9 position for methylation.…”
Section: Accounts Ofmentioning
confidence: 99%
“…Recently, intrinsic tRNA flexibility and enzyme-induced specific tRNA conformational change were found to be key factors for the discrimination of substrate between structurally similar tRNA species by Trm10p for methylation [124]. The conformational changes of substrate tRNA observed by using a sensitive RNA structure-probing method mainly lead to the increased reactivity in the D loop and decreased reactivity in the anticodon loop, which presumably position the target nucleotide in the binding pocket of Trm10p.…”
Section: Functions Of Yeast Trm10pmentioning
confidence: 99%